Systemic mastocytosis with terminal leukemic manifestation in two dogs - Ecco, Roselene; Assumpção, Anna L. F. V.; Couto, Rodrigo M.; Neto, Rachel L. A. L. T.; Valente, Pâmela C. L. G.; Gamba, Conrado O.; Leme, Fabiola O. P.; Paes, Paulo R. O. (Brazilian Journal of Veterinary Pathology, 2017)
Systemic mastocytosis (SM) with leukemic manifestation is rarely reported in veterinary patients. Here, we describe two cases of systemic mastocytosis with leukemic spread of neoplastic mast cells in adult dogs, including their clinical signs, clinical and anatomic pathology, and immunohistochemical analysis of c-KIT as a diagnostic tool. In both cases, hematologic examination revealed normocytic and normochromic anaemia, leucocytosis with segmented neutrophils, and mastocytosis. Cytological analyses of the peritoneal fluid revealed many neoplastic mast cells. Case 1 was associated with a subcutaneous mast cell tumor and Case 2 was not associated with a cutaneous or subcutaneous mast cell tumor. Neoplastic mast cells were found in the lymph nodes, spleen, liver, and kidneys, and a diagnosis of visceral mastocytosis was established. SM with terminal leukemic manifestation was confirmed by the mastocythemia intensity associated with the morphological changes of the mast cells in the blood and bone marrow.